Return of Case Files in Pre-Prosecution of Child Abuse Crimes - Polantia Ibrahim (Estudiante Law Journal, 2023)
The purpose of this research is to know and analyze aboutThe inhibiting factor of the case file cannot be delegated to the prosecution stage by the prosecutor at the Gorontalo District Attorney.This research uses a type of empirical legal research that uses facts in the field as the main data in compiling the research. Research results The inhibiting factor of the case file cannot be delegated to the prosecution stage by the prosecutor at the Gorontalo District Attorney's Office, namely the first factor is the unfulfilled formal requirements referred to namely visum et repertum whose contents do not refer to the crime of child molestation so that the prosecutor considers the case file difficult to process. charged at a later trial which may lead to consequences. Second, from the factor of material requirements, namely the Minutes of Examination (BAP) are not focused, the Investigator has not properly ensnared the article, the evidence is not completely listed, the witness statements are not completely listed, the modus operandi is not clearly stated.